2020
DOI: 10.1002/chem.202002655
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Host Molecule Bearing Pyridine Core for Highly Efficient Blue Thermally Activated Delayed Fluorescence OLEDs

Abstract: In this study,t wo host materials, pCzBzbCz and pCzPybCz,a re synthesized to achieve ah ighe fficiency and long lifetimeo fb lue thermally activated delayed fluorescence organic light-emitting diodes (TADF-OLEDs). The molecular design strategy involves the introduction of ap yridine group into the core structure of pCzPybCz as an electron-withdrawingu nit, anda ne lectron-donating phenyl group into the structure of pCzBzbCz.T hese host materials demonstrate good thermals tability and high triplet energy (T 1 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Based on its absorption extending between 300 and 450 nm with an absorption maximum located at 373 nm, this dye was thus appropriate for photopolymerization experiments carried out at 365, 385, and 405 nm (See Figure 2). effect transistors [213,214], the design of fluorescent materials [215] and light-emitting materials [216,217] or host materials [218] for organic light-emitting diodes. Furan exhibits a low toxicity, even if recent reports have demonstrated that furan can be formed during the thermal treatment of food and can be carcinogenic [219].…”
Section: Benzylidene Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its absorption extending between 300 and 450 nm with an absorption maximum located at 373 nm, this dye was thus appropriate for photopolymerization experiments carried out at 365, 385, and 405 nm (See Figure 2). effect transistors [213,214], the design of fluorescent materials [215] and light-emitting materials [216,217] or host materials [218] for organic light-emitting diodes. Furan exhibits a low toxicity, even if recent reports have demonstrated that furan can be formed during the thermal treatment of food and can be carcinogenic [219].…”
Section: Benzylidene Ketonesmentioning
confidence: 99%
“…Furan is a heterocyclic five-membered ring that is extensively used for the design of anti-inflammatory and antimicrobial agents [211]. Furan was also used for the design of semi-conducting materials for organic solar cells [212] and field effect transistors [213,214], the design of fluorescent materials [215] and light-emitting materials [216,217] or host materials [218] for organic light-emitting diodes. Furan exhibits a low toxicity, even if recent reports have demonstrated that furan can be formed during the thermal treatment of food and Catalysts 2023, 13, 493 3 of 28 can be carcinogenic [219].…”
Section: Introductionmentioning
confidence: 99%
“…However, a couple TADF-based OLEDs show a fair lifetime with high current efficacy in the sky-blue region. Yoon et al reported a lifetime of 24 h and CE max of 42 cd/A corresponding to a CIE y of 0.35 by using a 30 wt% DBA-BI emitter doped in a pCzPybCz host [ 113 ].…”
Section: Performance Statusmentioning
confidence: 99%
“…Several other carbazole and pyridine derivatives were successfully applied in OLEDs. 24–26 However, they were typically used as charge-transporting materials and as hosts. 27,28 The derivatives of carbazole and pyridine were reported as emitters for ultraviolet OLEDs with electroluminescence (EL) peaking at 394 nm and a narrow full-width at half maximum (FWHM) of 17 nm.…”
Section: Introductionmentioning
confidence: 99%